2010
DOI: 10.1007/s00441-010-1032-2
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte and macrophage heterogeneity and Toll-like receptors in the lung

Abstract: Mononuclear phagocytes are crucial components of the innate host defense system. Cells such as macrophages and monocytes phagocytose and process pathogens, produce inflammatory mediators, and link the innate and the adaptive immune systems. The role of innate immune receptors such as Toll-like receptors (TLRs) in the recognition of pathogens is critical for mounting a precise and targeted immune response. This review focuses attention on the development of monocytes and macrophages, various populations of macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 131 publications
1
54
0
2
Order By: Relevance
“…Only the thin alveolar wall separates alveolar from interstitial macrophages, which occupy the same narrow interalveolar space as alveolar capillaries, fibroblasts and other mesenchymal cells. Interstitial macrophages are thought to have roles in tissue remodeling and maintenance as well as antigen presentation (Aguzzi et al, 2013;Higashi et al, 1992;Lichanska and Hume, 2000;Robinson, 1984;Schneberger et al, 2011;Takeya and Takahashi, 1992), and influencing dendritic cell functions to prevent airway allergy (Bedoret et al, 2009;Ginhoux et al, 2010;den Haan and Kraal, 2012;Shibata et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Only the thin alveolar wall separates alveolar from interstitial macrophages, which occupy the same narrow interalveolar space as alveolar capillaries, fibroblasts and other mesenchymal cells. Interstitial macrophages are thought to have roles in tissue remodeling and maintenance as well as antigen presentation (Aguzzi et al, 2013;Higashi et al, 1992;Lichanska and Hume, 2000;Robinson, 1984;Schneberger et al, 2011;Takeya and Takahashi, 1992), and influencing dendritic cell functions to prevent airway allergy (Bedoret et al, 2009;Ginhoux et al, 2010;den Haan and Kraal, 2012;Shibata et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Alveolar macrophages also release transforming growth factor (TGF)-β, which inhibits immune responses by preventing dendritic cell-mediated activation of effector T-cells [4,14,15]. In addition, alveolar macrophages express several scavenger receptors that bind complement, damage-associated molecular pattern molecules, pathogen-associated molecular pattern molecules and immunoglobulins to facilitate pathogen clearance [2,16].…”
mentioning
confidence: 99%
“…Although monocyte-derived macrophages are in general a good model to study macrophage behaviour, previous studies have shown that these cellular subsets in vitro might not always represents alveolar macrophages in vivo [8,50]. Therefore, theoretically it is still possible that alveolar macrophages are a source of polymers within the lung in vivo, although the levels secreted by MM alveolar macrophages are comparable with monocytes and monocyte-derived macrophages in vitro [8,42].…”
Section: Discussionmentioning
confidence: 91%